Determinants of Short-Term Debt - Lusine Lusinyan; Claudia M. Buch (Kiel Institute of World Economics (IfW), 2000)
One key focus of the on-going debate on the integration of international financial markets have been measures to lengthen the maturity of foreign debt. Short-term debt is typically considered to be volatile and thus a potential trigger of currency crises. In contrast to the vivid policy debate on these issues, there is relatively little theoretical and empirical evidence on the determinants of short-term debt. This paper summarizes the theoretical literature on the issue and presents a stylized theoretical model, which focuses on the risks and benefits of short-term debt under conditions of uncertainty. Empirical evidence shows that the level of economic development, the presence of financial centres, and the share of loans to banks have a positive impact on the share of short-term loans. OECD membership, in contrast, has a negative influence.
Keywords: F21; F23; G21; 330; foreign debt maturity; Auslandsverschuldung; Laufzeit; Geldmarktpapier; Internationale Kapitalmobilität; Kreditrisiko; Liquide Mittel; Schätzung; Sozialprodukt; Finanzplatz; Eigenkapitalvorschriften; Theorie; Welt